MENGAPA TEOLOGI REFORMED? - Stephen Tong (Verbum Christi: Jurnal Teologi Reformed Injili, 2014)
This article assesses several important questions of challenges of Reformed movement and the evaluations toward this movement in the world. These questions would then be answered comprehensively. Christianity is the truth, therefore one embraces Christianity, this is not true in reverse. True Christianity is represented by Reformed Theology. The reason behind this statement is because Reformed Theology represents the Word of God and is faithful to this. Therefore, true movement in history is Reformed movement. The struggle to uphold Reformed Theology through Reformed movement is a warfare or a battle that needs to be done fervently. Reformed movement must also be a fiery movement and a combination to achieve high quality and large quantity.?